Pembelajaran Tutor Sebaya Dalam Upaya Meningkatkan Hasil Belajar Matematika Materi Operasi Hitung Bilangan Bulat Pada Siswa Kelas VI SDN 1 Sumberejo, Kemiling, Bandar Lampung - Sarifah Sarifah (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2021)
: One of the goals of learning mathematics in elementary school is to train thinking and reasoning in drawing conclusions, for example through investigation, exploration, experimentation, showing similarities, differences, consistent and inconsistent and developing creative activities that involve imagination, intuition, and discovery. by developing divergent thinking, originality, curiosity, making predictions and guesses, experimenting and problem solving skills. Based on the reflection of the sixth grade teacher at SDN 1 Sumberejo Kemiling, teachers often use the lecture method and assign assignments. Teachers have not used innovative and creative approaches, methods, or learning models. This causes students to be less enthusiastic about learning mathematics because they are only passive learning objects and only do the tasks given by the teacher. Problem solving used in this research is to apply peer tutor learning methods. This research is a classroom action research which consists of 3 cycles. The research subjects were teachers (researchers) and sixth grade students at SDN 1 Sumberejo Kemiling Bandar Lampung with a total of 28 students. As an observer, the researcher's colleagues were chosen. The variable of this research is Learning Outcomes. Data were collected using test and non-test techniques. Data analysis used quantitative and qualitative descriptive analysis. The results showed that through the implementation of the tutor method, it can improve the quality of mathematics learning in integer arithmetic operations for sixth grade students at SDN 1 Sumberejo Kemiling Bandar Lampung in the 2018/2019 school year. Suggestions from researchers are (1) creating a harmonious and pleasant atmosphere so that it can motivate students to be active in developing their abilities; (2) Teachers can apply peer tutoring methods as an alternative to improve the quality of teacher teaching in a lesson, especially in learning mathematics.